Design of a durable roof slab insulation system for tropical climatic conditions. Issue 1 (31st December 2016) - Nandapala, Kasun; Halwatura, Rangika
Abstract : Flat roof slabs become popular day-by-day due to the advantages like cyclonic resistance, the possibility of future vertical extension, and the possibility of utilizing as an additional working space. However, a serious matter of concern is its thermal discomfort, for which air conditioning is used as the most common remedy. This has led to extensive use of energy, increasing the operational cost of the buildings, and contributing to global warming. Hence, the current trend is to go for passive techniques. Insulating roof slabs is identified as a better passive way to make buildings thermally comfortable. In this study, several existing roof slab insulation systems and their performances were investigated, and the most effective system for tropical climates was identified. Since that system had an issue in durability, a new system was developed with a discontinued-stripped supporting arrangement, which withstood a 4MT-point load. Further, it was proven by comparing literature that the newly designed system has a heat gain reduction of more than 75%.